2024
DOI: 10.25100/cm.v42i3.887
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between knowledge society, research methodology, and student scientific production in medical students in Chile

Abstract: The literature proposes that the scientific production of the students of medicine and health sciences in Latin American countries is very poor and contradicts one of the key functions of universities when the concept of Knowledge Society is taken into account. The sequential and systematic application of courses related with the Research Methodology decreased the unsatisfactory indicators when applied to students at the Fines Terrae University Medical School (Chile). It was observed that those students who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In Table 4 [ 10 - 16 ], we note that, except for the Chilean study by Díaz [ 11 ], all the experiences identified originate from the United States. Given that medical education in the U.S. takes place at the postgraduate level, research training is integral to it.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 4 [ 10 - 16 ], we note that, except for the Chilean study by Díaz [ 11 ], all the experiences identified originate from the United States. Given that medical education in the U.S. takes place at the postgraduate level, research training is integral to it.…”
Section: Reviewmentioning
confidence: 99%
“…Hence, through the successful experiences detailed in the mapped articles, it was possible to ascertain how advanced they are in terms of research education. Two articles mapped (Table 4 ) focused exclusively on the student body [ 11 , 15 ] and highlighted the qualitative gains achieved by students who experienced research in a processual manner during their undergraduate studies.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4 [10-16], we note that, except for the Chilean study by Díaz [11], all the experiences identified originate from the United States. Given that medical education in the U.S. takes place at the postgraduate level, research training is integral to it.…”
Section: What the Case Studies Saymentioning
confidence: 99%